Examining The Risk Mitigation Strategies Of Farm Households In Ghana: The Role Of Community Water Resources. - Martey, E.; Asante-Addo, C.; Suraj, M.M.; et al (Elsevier Ltd, 2024)
Agricultural water is indispensable for fostering resilient and sustainable agricultural practices. However, empirical evidence regarding the relationship between community water resources (CWR) and risk mitigation behaviours among farm households remains scant. Utilising nationally-representative household survey data and geospatial information on household locations, we investigate how access to CWR influences crop diversification and sharecropping. By employing instrumental variable techniques and conducting various robustness checks to address potential endogeneity concerns, our results consistently show that communities with access to water resources experience greater crop diversification and reduced sharecropping compared to those with limited access. This effect is particularly pronounced among male-headed, youth-headed, and smallholder farm households in the northern zone. While CWR may not be the sole determinant of crop diversification and sharecropping, it plays a significant role in shaping adaptive strategies amid drought challenges. Moreover, we identify committed time as a critical mechanism through which CWR influences these outcomes. Our findings offer valuable insights for policymakers aiming to allocate resources effectively, especially for vulnerable populations, in enhancing resilience to climate change-induced water scarcity.
Research Article
Keywords: Community Water Resource; Crop Diversification; Sharecropping; Committed Time; Ghana